Does Gallery Lighting Really Have an Impact on Appreciation of Art? An Ecologically Valid Study of Lighting Changes and the Assessment and Emotional Experience With Representational and Abstract Paintings - Pelowski, Matthew; Graser, Andrea; Specker, Eva; Forster, Michael; von Hinüber, Josefine; Leder, Helmut (Frontiers in Psychology, 2019)
We report three studies considering the potential for gallery lighting conditions to modulate appraisals and emotional experience with works of visual art. As recently documented in a burgeoning number of papers, art appreciation represents a complex blend of formal artwork factors, personality and background of viewers, and multiple aspects of context regarding where and how art is experienced. Among the latter, lighting would be expected to play a fundamental role. However, surprisingly this has received little empirical assessment with almost no ecologically valid gallery analyses. Here, we employed a controlled paradigm using a spontaneous art viewing context, gallery-like setting, and a proprietary lighting system which allowed the minute adjustment of lighting intensity/temperature. Participants viewed a selection of original representational and abstract art under three different light conditions (Study 1), modulated between participants so as to minimize awareness of the actual lighting changes, and reported ratings using a number of scales. The selected lighting temperatures were chosen, based on an initial investigation of existing art museums within the Vienna area, addressing how they themselves light their art—a question which, also somewhat surprisingly, has not often been considered. We also allowed the same participants to set the light temperature themselves in order to test hypotheses regarding what conditions might be ideal as derived by the actual novice viewers. In Study 2, we explored the question of whether artworks made by an artist to match specific lighting conditions show a resulting connection to the ratings of individuals when shown in the same or different conditions. Results showed almost no effects from lighting changes in both studies. Viewers’ self-set light temperature (mean = 3777K) did roughly coincide with the suggested most enjoyable conditions for everyday living and some past art research on art viewing, but again showed a wide interpersonal variance. Results, and a general review of lighting factors are considered in order to provide art researchers and curators with a tool for conducting future research